The Chinese Society of Clinical Oncology (CSCO): Clinical guidelines for the diagnosis and treatment of gastric cancer, 2021 - Wang, Feng‐Hua; Zhang, Xiao‐Tian; Li, Yuan‐Fang; Tang, Lei; Qu, Xiu‐Juan; Ying, Jie‐Er; Zhang, Jun; Sun, Ling‐Yu; Lin, Rong‐Bo; Qiu, Hong; Wang, Chang; Qiu, Miao‐Zhen; et al. (Cancer communications (London, England), 2021)
There exist differences in the epidemiological characteristics, clinicopathological features, tumor biological characteristics, treatment patterns, and drug selections between gastric cancer patients from the Eastern and Western countries. The Chinese Society of Clinical Oncology (CSCO) has organized a panel of senior experts specializing in all sub‐specialties of gastric cancer to compile a clinical guideline for the diagnosis and treatment of gastric cancer since 2016 and renews it annually. Taking into account regional differences, giving full consideration to the accessibility of diagnosis and treatment resources, these experts have conducted expert consensus judgment on relevant evidence and made various grades of recommendations for the clinical diagnosis and treatment of gastric cancer to reflect the value of cancer treatment and meeting health economic indexes in China. The 2021 CSCO Clinical Practice Guidelines for Gastric Cancer covers the diagnosis, treatment, follow‐up, and screening of gastric cancer. Based on the 2020 version of the CSCO Chinese Gastric Cancer guidelines, this updated guideline integrates the results of major clinical studies from China and overseas for the past year, focused on the inclusion of research data from the Chinese population for more personalized and clinically relevant recommendations. For the comprehensive treatment of non‐metastatic gastric cancer, attentions were paid to neoadjuvant treatment. The value of perioperative chemotherapy is gradually becoming clearer and its recommendation level has been updated. For the comprehensive treatment of metastatic gastric cancer, recommendations for immunotherapy were included, and immune checkpoint inhibitors from third‐line to the first‐line of treatment for different patient groups with detailed notes are provided. The Chinese Society of Clinical Oncology (CSCO) organized a panel of senior experts specializing in all sub‐specialties of gastric cancer to compile the clinical guideline for gastric cancer in 2016 and then renewed it every year. The 2021 CSCO Clinical Practice Guidelines for gastric cancer covered the diagnosis, treatment, follow‐up and screening.